A survey study investigating perceptions and acceptance of the whole-body imaging techniques used for the diagnosis of myeloma. Issue 4 (November 2021) - Ryder, A.; Parsons, C.; Hutchinson, C.E.; Greaney, B.; Thake, C.D.
Abstract: Introduction: The purpose of this study was to investigate patient perceptions and acceptance of the three whole-body imaging (WBI) modalities used for diagnosing myeloma; radiographic skeletal survey (RSS), low-dose whole-body computed tomography (LD-WBCT) and whole-body magnetic resonance imaging (WB-MRI). The secondary aim was to explore the factors affecting the acceptance of whole-body imaging for myeloma. Methods: 60 participants (median age = 58.5 years old) recruited from three NHS trusts and social media completed a survey in which they scored their experiences of each WBI modality on nine 5-point rating scales. Spearman's correlation coefficient, Kruskal–Wallis, Mann–Whitney and Wilcoxon signed-rank tests were used to compare scores between different WBI techniques. Participants were invited to provide additional open text responses for interpretation using thematic analysis. Results: All modalities demonstrated high levels of acceptability (median score = 4). WB-MRI was perceived as more stressful ( p =<0.01) and claustrophobic ( p =<0.01) than RSS and LD-WBCT. Thematic analysis showed patients understood the importance of imaging but had concerns about exacerbated pain and the results. WB-MRI was difficult to tolerate due to its duration. Respondents were averse to the physical manipulation required for RSS while remaining stationary was perceived as a benefit of LD-WBCT and WB-MRI. Staff interactions had both positive and negative effects on acceptance. Conclusions: Despite the psychological and physical burdens of WBI, patients accepted its role in facilitating diagnosis. Staff support is vital for facilitating a positive whole-body imaging experience. Healthcare practitioners can improve WBI acceptance by understanding the burdens imposed by WBI and adopting the personalised care model. Implications for practice: Patient experience can be improved by tailoring examinations to individual needs. RSS can be as burdensome as other WBI techniques and could be superseded by LD-WBCT or WB-MRI.